2010
DOI: 10.1007/s12272-010-0209-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Puerarin on CYP2D6 and CYP1A2 activities In vivo

Abstract: Ge-gen (Radix Puerariae) is used in traditional oriental medicine for various medicinal purposes. The drug is the root of a wild leguminous creeper, Pueraria lobata (Willd) Ohwi. It possesses a high content of avonoid derivatives, the most abundant of which is puerarin. Our goal was to find the effect of puerarin on cytochrome P450 enzymes in vivo. The study was conducted in 18 male volunteers of different genotypes (CYP2D6 *1/*1, *1/*10, *10/*10). Plasma was obtained at 6 h after oral administration and urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…An in vitro study showed puerarin and Radix Puerariae extract could enhance the activity of some cytochrome P450 enzymes, such as CYP 1A1/2, CYP 2A1, CYP 2C11, and inhibit CYP 2B1, CYP 2E1, and CYP 3A in Wistar rats . In addition, a clinical trial in vivo study indicated puerarin induced the expression of CYP 1A2 and inhibit the activity of CYP 2D6 . These findings suggests Radix Puerariae or its products, such as puerarin, extract or total flavones, may change the metabolism of substrates of the above mentioned CYP isoenzymes.…”
Section: Herb–drug Interactionsmentioning
confidence: 88%
“…An in vitro study showed puerarin and Radix Puerariae extract could enhance the activity of some cytochrome P450 enzymes, such as CYP 1A1/2, CYP 2A1, CYP 2C11, and inhibit CYP 2B1, CYP 2E1, and CYP 3A in Wistar rats . In addition, a clinical trial in vivo study indicated puerarin induced the expression of CYP 1A2 and inhibit the activity of CYP 2D6 . These findings suggests Radix Puerariae or its products, such as puerarin, extract or total flavones, may change the metabolism of substrates of the above mentioned CYP isoenzymes.…”
Section: Herb–drug Interactionsmentioning
confidence: 88%
“…The 12 h pharmacokinetics of omeprazole, midazolam, caffeine, and 0–8 h losartan/E-3174 as well as dextromethorphan/dextrorphan urinary ratio were measured. Midazolam/1′-hydroxymidazolam ratio at 1 h, caffeine/paraxanthine ratio at 6 h, and omeprazole/5′-hydroxyomeprazole ratio at 4 h in plasma were used as extra phenotypic indices [68] for quantifying corresponding enzyme activity change. Blood and urine samples were prepared as previously reported [6].…”
Section: Methodsmentioning
confidence: 99%
“…Puerarin (400 mg/d, i.v.) was given to eighteen healthy Chinese male volunteers for 10 days, and induced the expression of CYP 1A2 and declined the activity of CYP 2D6 (Zheng et al, 2010). In addition, administration of puerarin (200 mg/kg, i.g.)…”
Section: Potential Herb-drug Interactionsmentioning
confidence: 99%